Change in Hepatitis A Seroprevalence among U.S. Children and Adolescents: Results from the National Health and Nutrition Examination Survey 2003–2006 and 2007–2010 - Kruszon-Moran, Deanna (Vaccines (Basel), 2013)
To examine changes in seroprevalence of antibodies to hepatitis A virus (HAV) during a period in which universal vaccine recommendations for all U.S. children were implemented, results from serologic testing from the National Health and Nutrition Examination Survey (NHANES) from 2003–2010 were analyzed among 7,989 participants age 6–19 years, born in the U.S. in two birth cohorts (1986–1996 and 1997–2004). Overall prevalence increased over time from 24.4% in 2003–2006 to the highest ever reported (37.6%) in 2007–2010. Specifically, increases reached statistical significance in the birth cohort born in the years after implementation of vaccine recommendations (1997–2004), among those of race/ethnicity other than white, non-Hispanic, and among states where recommendations were implemented later. The greatest increase over time was among the subgroup of persons in states with early implementation who were of race/ethnicity other than white, non-Hispanic. Geographic region and birth cohort based on vaccine recommendations as well as race/ethnicity were the main predictors of seropositivity in 2007–2010. The increase in Hepatitis A seroprevalence occurred during a time of decreasing incidence and increasing vaccination, however race/ethnic disparities persist.